2021
DOI: 10.2174/2212797613999200728190605
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Materials of System-in-Package: A Review

Abstract: Background: As a new type of advanced packaging and system integration technology, System-in-Package (SiP) can realize the miniaturization and multi-functionalization of electronic products and is listed as an important direction of development by International Technology Roadmap for Semiconductors (ITRS). <P> Objective: This paper mainly introduces and discusses recent academic research and patents on package structure and packaging materials. Additionally, the trending of development is described. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Researchers’ studies on delamination mechanisms have mainly focused on thermal stress damage and moisture damage. Explaining the delamination phenomenon from the stress–strain perspective alone, it has been found that, at the delamination interface, mainly due to the interface between the two phases of the material, the plastic deformation of the two-phase material is formed under the action of the alternating shear stress, which ultimately leads to the failure of delamination [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. At the same time, under the intrusion of moisture, ionic contaminants corrode the chip, and moisture thermal expansion is also the main reason for the device to appear to suffer from the “popcorn” effect [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers’ studies on delamination mechanisms have mainly focused on thermal stress damage and moisture damage. Explaining the delamination phenomenon from the stress–strain perspective alone, it has been found that, at the delamination interface, mainly due to the interface between the two phases of the material, the plastic deformation of the two-phase material is formed under the action of the alternating shear stress, which ultimately leads to the failure of delamination [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. At the same time, under the intrusion of moisture, ionic contaminants corrode the chip, and moisture thermal expansion is also the main reason for the device to appear to suffer from the “popcorn” effect [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, its production and quality inspection technology become particularly important. As the chip carrier of integrated circuit, the semiconductor lead frame is a key structural part that can realize the electrical connection between the internal circuit lead and the external lead by means of bonding materials (gold wire, aluminum wire, copper wire) and form an electrical circuit [4][5][6]. Its main functions include connection with external circuits, heat dissipation, mechanical support, etc.…”
Section: Introductionmentioning
confidence: 99%